Downstream processing of Beauveria bassiana and Metarhizium anisopliae-based fungal biopesticides against Riptortus pedestris: solid culture and delivery of conidia. Issue 6 (3rd June 2019) - Song, Min Ho; Yu, Jeong Seon; Kim, Sihyeon; Lee, Se Jin; Kim, Jong Cheol; Nai, Yu-Shin; Shin, Tae Young; Kim, Jae Su
ABSTRACT: We established a fungal production platform by focusing on substrates of solid culture for conidial productivity and thermotolerance, and focusing on surfactants to effectively deliver fungal conidia to the Riptortus pedestris cuticles. First, to produce thermotolerant fungal conidia, 2 of each Beauveria bassiana and Metarhizium anisopliae isolates were cultured on 13 cereal substrates for 10 days. Overall, five substrates (millet, non-glutinous Italian foxtail millet, barley, glutinous Italian foxtail millet, and brown rice) produced greatest number of conidia with thermotolerant conidia. When the selected substrates were mixed with minerals, zeolite, perlite or vermiculite to reduce the amount of cereal grains, vermiculite combination showed relatively high conidial production compared to the other mineral combinations. Next, to efficiently deliver the fungal conidia to the cuticles of R. pedestris, six surfactants, CO-2.5, CO-12, LE-7, PE-61, TED-3, and siloxane were each combined with the fungal conidia. The 0.01% combination showed significantly increased insect mortality, which varied depending on isolate. Virulence tests against R. pedestris were performed with conidial suspensions of isolates to assess their virulence. As a result, isolates showed the highest virulence when a virulence test was conducted at 25°C, rather than 20°C, 30°C and 35°C. This work suggests that the combination of cereal grain substrates and vermiculite could be considered for economic conidial production with high thermotolerance, and the CO-12 surfactant is the most suitable for effective delivery to target insects, followed by the information on optimal temperature for virulence against R. pedestris .